Study on the Synchronistic King List from Ashur - Chen, Fei (Cuneiform monographs, 2020)
Front Matter -- Copyright page -- Dedication -- Preface -- Acknowledgements -- Tables -- Abbreviations -- Introduction -- The Texts of the Synchronistic King List -- The Format of the Synchronistic King List -- The Composition of the Synchronistic King List -- The Purpose of the Synchronistic King List -- Conclusion -- Back Matter -- A List of Assyrian Kings -- A List of Babylonian Kings -- The Selected Synchronistic Kings of Assyria and Babylonia in the Lacunae of A.117 -- Bibliography -- Plates -- Index of Personal Names.